PENGEMBANGAN LONGEST PATH ALGORITHM (LPA) DALAM RANGKA PENCARIAN LINTASAN TERPANJANG PADA GRAF BERSAMBUNG BERARAH BERUNTAI - Oliver Samuel Simanjuntak (Telematika, 2012)
The longest distance in a graph that has a number of vertices, arcs and small strands easily done manually. However, if the graph has a number of vertices, arcs and strands of many, the determination of the distance and the longest path will be difficult. Research has developed Longest Path Algorithm (LPA) in order to search for the longest distance and trajectory continued trending stranded on a graph. LPA enables application development and search distance of the longest path in the graph continued trending quickly and accurately. LPA in the development of a solution to help solve the problem of finding the longest path in a directed graph stranded concatenated.